Elevated aortic pulse wave velocity, a marker of arterial stiffness, predicts cardiovascular events in well-functioning older adults - Sutton-Tyrrell, Kim; Najjar, Samer S; Boudreau, Robert M; Venkitachalam, Lakshmi; Kupelian, Varant; Simonsick, Eleanor M; Havlik, Richard; Lakatta, Edward G; Spurgeon, Harold; Kritchevsky, Stephen; Pahor, Marco; Bauer, Douglas; et al. (Circulation (New York, N.Y.), 2005)
Aging results in vascular stiffening and an increase in the velocity of the pressure wave as it travels down the aorta. Increased aortic pulse wave velocity (aPWV) has been associated with mortality in clinical but not general populations. The objective of this investigation was to determine whether aPWV is associated with total and cardiovascular (CV) mortality and CV events in a community-dwelling sample of older adults. aPWV was measured at baseline in 2488 participants from the Health, Aging and Body Composition (Health ABC) study. Vital status, cause of death and coronary heart disease (CHD), stroke, and congestive heart failure were determined from medical records. Over 4.6 years, 265 deaths occurred, 111 as a result of cardiovascular causes. There were 341 CHD events, 94 stroke events, and 181 cases of congestive heart failure. Results are presented by quartiles because of a threshold effect between the first and second aPWV quartiles. Higher aPWV was associated with both total mortality (relative risk, 1.5, 1.6, and 1.7 for aPWV quartiles 2, 3, and 4 versus 1; P=0.019) and cardiovascular mortality (relative risk, 2.1, 3.0, and 2.3 for quartiles 2, 3, and 4 versus 1; P=0.004). aPWV quartile was also significantly associated with CHD (P=0.007) and stroke (P=0.001). These associations remained after adjustment for age, gender, race, systolic blood pressure, known CV disease, and other variables related to events. Among generally healthy, community-dwelling older adults, aPWV, a marker of arterial stiffness, is associated with higher CV mortality, CHD, and stroke.